Of Narrators and Legs: Representing Bodies in the Victorian Novel. - Hueso-Vasallo, Manuel (My University, 2016)
From the last decades of the twentieth century onwards, the representational value of the human body in literature has been an important component of literary criticism. In the field of Victorianism, for instance, many of the most significant literary studies carried out during the 90s deal with the body. Seminal studies such as Anne Cvetkovich’s Mixed Feelings (1992), a re-definition of Sensation Fiction and its perceived dangers, and Sally Shuttleworth’s Charlotte Brontë and Victorian Psychology (1996), a mapping of Victorian psychology in literary texts, have had the body, both of readers, characters, and authors, at their core. In this paper I seek to re-address Victorian novels by positioning the theories at work within Disability Studies alongside Victorian popular (pseudo)scientific notions of the body, to show how a methodology that uses this seemingly anachronistic combination of frameworks may be, in fact, interdependent and beneficial to study the concept of the body, and relevant to a re-thinking of Victorian texts.
Keywords: Literatura inglesa - S. XIX; Personas con discapacidad - En la literatura; Disability studies; Victorian literature